2013
DOI: 10.1155/2013/482370
|View full text |Cite
|
Sign up to set email alerts
|

Delay in Diagnosis of Adrenal Insufficiency Is a Frequent Cause of Adrenal Crisis

Abstract: Delay of diagnosis of primary adrenal insufficiency (PAI) leads to adrenal crisis which is potentially lethal complication. The objective of our work was an assessment whether the establishment of diagnosis of adrenocortical insufficiency in Poland is so much delayed as assessed in the past. We have analysed data from 60 patients with diagnosis of PAI established in our department during the past 12 years and who are still under our care. We found that the time to diagnosis of primary adrenal insufficiency in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 12 publications
0
40
0
3
Order By: Relevance
“…28,29 Medical staff is to be repeatedly alerted for the management of this complication. 27,30 Our data demonstrate impressively that patients with APS, and especially those with PAI and type 1 diabetes mellitus, are at highest risk for adrenal crises and must be considered as an extremely vulnerable subgroup. Based on our data, we can calculate the number of patients with PAI and type 1 diabetes at around 550 in Germany, 3450 in the EU, respectively, 2150 in the United States.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…28,29 Medical staff is to be repeatedly alerted for the management of this complication. 27,30 Our data demonstrate impressively that patients with APS, and especially those with PAI and type 1 diabetes mellitus, are at highest risk for adrenal crises and must be considered as an extremely vulnerable subgroup. Based on our data, we can calculate the number of patients with PAI and type 1 diabetes at around 550 in Germany, 3450 in the EU, respectively, 2150 in the United States.…”
Section: Discussionmentioning
confidence: 74%
“…Every patient needs an emergency card containing instructions for the case of emergency and contact data of an experienced endocrinologist as well as an emergency kit comprising a hydrocortisone solution for parenteral administration and glucocorticoid suppositories, if applicable . Medical staff is to be repeatedly alerted for the management of this complication …”
Section: Discussionmentioning
confidence: 99%
“…In fact, it would be worthwhile to compare the collected data with those obtained in similar surveys in other hospitals; unfortunately, there is a lack of substantial data. Previous studies demonstrated that 45% of patients were diagnosed only after hospitalization due to an adrenal crisis despite prior evident signs of AI [9]. Bleicken et al demonstrated that 68% of patients with AI had an incorrect diagnose at first [10].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is possible that some admissions with a principal diagnosis of hypopituitarism related to patients with hormone deficiencies other than ACTH. Further, these data also do not enable determination of whether the presentation with an AC was the first occasion that AI was diagnosed in an individual, a phenomenon that happens in a significant proportion of patients [36]. These data also do not allow any differentiation between admissions for medical, surgical or investigative purposes.…”
Section: Discussionmentioning
confidence: 99%